Community-Based Waste Management in The Township PT. Bukit Asam, Tanjung Enim, Indonesia - Fitriani, Amelia; Windusari, Yuanita; Putri, Wike Ayu Eka (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
Community-based waste management in the PT. Bukit Asam Township, Tanjung Enim, is essential. This study involved 67 respondents residing in the Township. A mixed-method approach was used, including interviews, observations, and SWOT analysis. The results indicate that residents are actively engaged in waste containment, with most households (85%) disposing of all waste without sorting. Only a small percentage reuse items (5%) and compost (2%). The average waste generated per socioeconomic group exceeds the standards set by SNI 3242-2008. Community-based waste management at PT. Bukit Asam has the potential for success due to active participation and company support. The SWOT analysis reveals strengths in participation, company support, education, and a structured system but weaknesses in dependence on participation and funding, and limitations in human resources and infrastructure. Opportunities include government support, new technologies, and collaboration with NGOs, while threats arise from policy changes, social issues, regulations, environmental impacts, and disasters. Improvement strategies include initial assessments, stakeholder mapping, awareness enhancement, facility provision, supervision, monitoring, incentives, periodic evaluations, and continuous innovation. With these strategies, the program is expected to be effective and sustainable, address waste issues, create new economic opportunities, and serve as a model for other communities.